CHANGE IN THE LATTICE STATUS OF FE IONS ON MELTING OF ALMANDINE FE3AL2SI3O12 - Bychkov A.M.; Polosin A.V.; Borisov A.A.; Agoshkov V.M.; Khodyrer O.Yu.; Guzhova A.V. (My University, 1989)
The authors showed earlier that on fusion of aegirine NaFeSi2O6 and kirschsteinite CaFeSiO4, the coordination numbers of Fe2+ and Fe3+ ions occupying octahedral positions in the crystals decrease to 4 and that these ions tend to take on the properties of framework-forming elements. In the present paper they present data on the Moessbauer spectroscopy of glasses obtained by quenching molten almandine. In this mineral of the garnet group, the Fe2+ ions have the highest coordination number found in silicates. Because almandine lacks such large cations as Na, K, Ca, Ba and the like, which function as typical modifiers on fusion, it is reasoned that the behavior of Fe ions on fusion of almandine would differ from that in the fusion of aegirine kirschsteinite.